UJI AKTIVITAS IMUNOSTIMULATOR FRAKSI AIR DARI EKSTRAK ETANOL KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) TERHADAP PROLIFERASI SEL LIMFOSIT MENCIT GALUR SWISS SECARA IN VITRO BESERTA IDENTIFIKASI KANDUNGAN KIMIANYA - Oktarina Heni Puspitowati; Maria Ulfah; Ediati Sasmito (Universitas Wahid Hasyim Semarang, 2012)
ABSTRACTRoselle calyx has been used as traditional medicine for generations. The content of phenols and flavonoids in the roselle calyx thought to have immunostimulatory effects. This study aims to determine the immunostimulatory activity in vitro and to identified phenolic and flavonoids compounds in the water fraction of roselle (Hibiscus sabdariffa L.) calyx ethanol extract.Powder of roselle calyx macerated with 96% ethanol. The extract were obtained partitioned gradually with n-hexana, ethyl acetate, and water. Immunostimulatory activity test was done according to MTT Assay with series of water fraction at concentration 10, 20, 50,100, 200, 400 μg/mL and positive control PHA 10 μg/ml against to lymphocyte cell culture. Optical Density (OD) data was statistically analyzed by Oneway ANOVA followed Tukey test (p<0.05). Identification of phenolic and flavonoids compounds in roselle calyx done by Thin Layer Chromatography (TLC).The results of statistical analysis showed that water fraction have immunostimulatory activity against lymphocyte proliferation at a concentration of 400 μg/mL were significantly different compared to the positive control and the cells control (p<0.05). TLC test results showed that the fraction contained phenols and flavonoids.Key words : roselle (Hibiscus sabdariffa L.) calyx, MTT Assay, immunostimulatory, phenolic and flavonoid.